Reducing the Risk of Seed-Borne Fungi Development of Foxtail Millet from Buru Island through Hot Water Treatment - PARLINDO, FITRA; Khairani, Hagia Sophia; Ardie, Sintho Wahyuning (Jurnal Fitopatologi Indonesia, 2023)
The use of fungi-free seeds is an important factor to increase the production of foxtail millet (Setaria italica). This study aims to develop a technique to eliminate seed-borne fungi of foxtail millet seeds from Buru Island through hot water treatment. Identification of seed-borne fungi showed that Boeremia sp. was the dominant fungus on foxtail millet seeds from Buru Island. Hot water treatment with a combination of temperature (50 ℃, 52 ℃, 54 ℃) and treatment period (15, 20, 25 minutes) was examined to determine the most effective treatment in suppressing the growth of fungi but not affecting seed germination. This study showed that hot water treatment at 50 ℃ for 25 minutes reduced fungal infestation in vitro and ad planta by 57% and 55%, respectively. This indicates that this method can be relied upon to save foxtail millet seed production losses due to the development of pathogenic fungi.